ISLAM IN THE CAUCASUS AND ITS IMPACT ON CONFLICT POTENTIAL IN THE REGION AND IN RUSSIA - Akhmet A. Yarlykanov (Сравнительная политика, 2015)
Islam in the Caucasus cannot be described in black and white colors as official and non-official, traditional and non-traditional Islam. Islam is now playing a more distinctive role in the social and political life of the republics in the North Caucasus. However, its role in the conflicts cannot be explained by Islam itself which plays the role of disguise for the real reasons of the conflicts. The article examines strengthening of Islam on the Caucasus, as well as its globalization, and politization and the rise of jihadism. It analyses complex relations among its many different forms and schools.